2013
DOI: 10.1007/s12061-013-9084-9
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship Between Neighborhood Perception, Length of Residence and Co-Ethnic Concentration

Abstract: We investigate how co-ethnic concentration and length of residence are related to neighborhood perception in aged Mexican Americans, and discuss sources of information for measuring social environments. Neighborhood perception scale, length of residence in current home, and all individual-level covariates in a hierarchical linear model are derived from data on community-dwelling older adults. Tract-level measures are obtained from Census data. We find no relationship between co-ethnic concentration and positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…This study also found that differences in length of residence had effects on residents' SSC and RSC. This is in line with previous research (Yamamura, 2011;Siordia and Saenz, 2013). The longer residents live in a neighborhood, the more likely they are to communicate with neighbors and develop trust.…”
Section: Theoretical Implicationssupporting
confidence: 92%
See 1 more Smart Citation
“…This study also found that differences in length of residence had effects on residents' SSC and RSC. This is in line with previous research (Yamamura, 2011;Siordia and Saenz, 2013). The longer residents live in a neighborhood, the more likely they are to communicate with neighbors and develop trust.…”
Section: Theoretical Implicationssupporting
confidence: 92%
“…Nyqvist et al (2016) confirmed the moderating role of age in social contact. Regarding length of residence, Siordia and Saenz (2013) suggested that residents with a long length of residence will have more positive neighborhood perceptions. Yamamura (2011) found that length of residence positively influenced investment in social capital.…”
Section: Relational Social Capital In Neighborhood Renewalmentioning
confidence: 99%
“…Hipp, 2010b), regions (e.g. the Southwest; Siordia and Saenz, 2013) and specific cities (e.g. Chicago; King, 2013).…”
Section: Who Gets Asked About Neighbourhood Satisfaction?mentioning
confidence: 99%
“…Many studies have documented significant associations between objective or subjective neighborhood factors and individual health outcomes, net of personal characteristics (see Balfour and Kaplan 2002;Clarke et al 2014;Diez Roux 2001;Do et al 2008;Ellaway, Macintyre, and Kearns 2001;Kawachi and Berkman 2003;Siordia and Saenz 2013;Wen, Hawkley, and Cacioppo 2006;Weden, Carpiano, and Robert 2008;Yen et al 2008). For example, the availability of recreational parks and bus routes has been found to be positively associated with levels of physical activity participation, thus indirectly promoting health.…”
Section: Literature Reviewmentioning
confidence: 99%